Feline asthma and heartworm disease: Clinical features, diagnostics and therapeutics. Issue 9 (September 2019) - Garrity, Sarah; Lee-Fowler, Tekla; Reinero, Carol
Practical relevance: For feline practitioners, the cat with a cough or respiratory distress and thoracic radiographs with a bronchial or bronchointerstitial pattern suggests lower airway disease. Two important differentials, allergic asthma and heartworm disease (HWD), have many overlapping clinicopathologic features, but also clear and important differences in terms of cause and disease progression, treatment and prognosis. Notably, asthma is readily treatable and HWD is preventable. Clinical significance: Feline HWD comprises two clinical syndromes: the comparatively recently described heartworm-associated respiratory disease (HARD) and adult HWD. The former is much more common; very few cats with HARD develop adult HWD. In HARD, following death of immature worms, pulmonary lesions may improve over time ('self-cure'). Lesions of adult HWD also improve over time as long as reinfection does not occur; however, with death of adult heartworms, mortality is high, and the prognosis is guarded. In asthma, morbidity is relatively high, but mortality is low, with an overall good to excellent prognosis. Disease recognition: Feline asthma is encountered worldwide. In the authors' impression, feline HWD is often under-recognized. Aims: The aim of this review is to assist clinicians in differentiating feline asthma from feline HWD; as such, the emphasis is on distinguishing clinical features, as well as on diagnostics, therapy and prognosis. In differentiating these conditions, clinicians can attempt the goal of properly managing these diseases and can best educate owners on prognosis. Evidence base: For both feline asthma and feline HWD, the authors have drawn on the available peer-reviewed literature studies involving experimental models as well as spontaneous disease.